Determinants of undernutrition among children aged 6 to 59 months in rural Zambézia Province, Mozambique: results of two population-based serial cross-sectional surveys. Issue 1 (December 2015) - Rose, Elizabeth; Blevins, Meridith; González-Calvo, Lazaro; Ndatimana, Elisée; Green, Ann; Lopez, Melanie; Olupona, Omo; Vermund, Sten; Moon, Troy
Abstract Background While many countries are transitioning from epidemics of undernutrition to overnutrition, Mozambique's very high 44 % prevalence of stunting in children under age 5 years is cause for serious concern. Methods We conducted two population-based cross-sectional surveys of ~4000 female heads of households each in Zambézia Province, Mozambique from August-September 2010 (Baseline) and April-May 2014 (Endline) as part of the USAID funded Strengthening Communities through Integrated Programs (SCIP) grant. Anthropometric measurements were collected on 560 children aged 6–59 months at Baseline and 912 children at Endline and classified as: "stunted, " a height-for-age z-score less than -2; "wasted, " weight-for-height z-score less than -2; and "underweight, " weight-for-age z-score less than -2. Descriptive statistics and logistic regression using Stata 13.1 were used to examine factors associated with undernutrition. Results Of children under age 5 years, 43 % were undernourished in 2010 and 55 % in 2014. The most common form of undernutrition was stunting (39 % in 2010, 51 % in 2014), followed by underweight (13 % in both 2010 and 2014), and wasting (7 % in 2010, 5 % in 2014). Child's age was found to have a non-linear association with stunting. Vitamin A supplementation was associated with a 31 % (p  = 0.04) decreased odds of stunting. Children who were exclusively breastfed for at least 6 months had an 80 % (p  = 0.02) lower odds of wasting in 2014 and 57 % (p  = 0.05) decreased odds of being underweight in 2014. Introducing other foods after age 6 months was associated with a five-fold increased odds of wasting in 2014 (p  = 0.02); household food insecurity was associated with wasting (OR = 2.08;p  = 0.03) and underweight in 2010 (OR = 2.31;p  = 0.05). Children whose mother washed her hands with a cleaning agent had a 40 % (p  = 0.05) decreased odds of being underweight. Surprisingly, per point increase in household dietary diversity score, children had 12 % greater odds of being stunted in 2010 (p  = 0.01) but 9 % decreased odds of being underweight in 2014 (p  = 0.02). Conclusions A combination of household and individual level factors was associated with undernutrition. As such, employment of multidimensional interventions should be considered to decrease undernutrition in children under 5 years old.